Clinically recorded heart rate and incidence of 12 coronary, cardiac, cerebrovascular and peripheral arterial diseases in 233, 970 men and women: A linked electronic health record study. (29th August 2020) - Archangelidi, Olga; Pujades-Rodriguez, Mar; Timmis, Adam; Jouven, Xavier; Denaxas, Spiros; Hemingway, Harry
Abstract: Background: In healthy population cohorts, resting heart rate above 90 bpm is associated with mortality from coronary heart disease, but it is not clear whether associations are present at lower heart rates or whether these associations differ between women. Methods: The CALIBER resource of linked electronic health records from primary care, hospitalisations, myocardial infarction registry and cause-specific mortality in the UK was used to assess associations between resting heart rate and 12 fatal and non-fatal coronary, cardiac, cerebral and peripheral vascular cardiovascular diseases and death using Cox proportional hazard models. Results: Among 233, 970 patients, 29, 690 fatal and non-fatal events occurred. Fully adjusted models showed that resting heart rate was not associated in men or women with cerebrovascular events. In men a resting heart rate of 70–79 bpm (29.1% of all men) versus less than 60 bpm was associated with an increased risk of heart failure (hazard ratio (HR) 1.65, 95% confidence interval (CI) 1.26–2.16), unheralded coronary death (HR 1.65, 95% CI 1.13–2.41), total cardiovascular events (HR 1.22, 95% CI 1.15–1.28) and all-cause mortality (HR 1.39, 95% CI 1.22–1.58). Women with a higher resting heart rate level of 80–89 bpm versus 60 bpm had a higher risk of total cardiovascular disease events (HR 1.17, 95% CI 1.07–1.24) and all-cause mortality (HR 1.21, 95% CI 1.07–1.35) compared to a resting heart rate less than 60 bpm. The risk was also present at higher heart rates (>90 bpm) for heart failure and sudden cardiac death. Conclusions: A resting heart rate that clinicians currently consider as 'normal' in the general population is specifically associated with the incidence of certain major cardiovascular diseases and death, with the risk starting at lower resting heart rate levels in men compared to women. Further research is required to evaluate whether interventions to lower resting heart rate are warranted to prevent disease. The study is registered at: clinicaltrials.gov (ID: NCT01947361).